Numeracy for teaching - Haylock, Derek (London : Paul Chapman : Thousand Oaks, Calif. : Sage Publications, 2001)
This book is designed to help teacher-trainees prepare for the Qualified Teaching Standards numeracy test that must now be passed by all entrants to the teaching profession. The author focuses especially on weaknesses in numeracy often observed in adults, and in teacher-trainees in particular. As far as possible, this mathematics is set in the professional context of teaching, drawing on statistics and other data from individual schools, the DfEE and the Qualifications and Curriculum Agency (QCA).
Includes bibliographical references.
Keywords: Numeracy -- Study and teaching (Elementary) -- England; Numeracy -- Problems, exercises, etc